Teacher illness: analysis of the profile of leave from work in the district division of the central-south zone of the municipal education department in Manaus-Am/Brazil (Research, Society and Development, 2022)
The teaching professional has, in his work environment, a place that sometimes presents itself as a wear factor, both physical and psychological. In this sense, constant interpersonal relationships and task overload are observed as conditioning factors. In addition, the precariousness with which they perform their functions demonstrates the psychophysical deterioration that results in the many cases of stress and illness among these professionals. In this light, this study has as main objective: to analyze the cases of teacher illness, from the analysis of the profile of absence from work, in the District Division of the Center-South Zone, of the Municipal Department of Education, in Manaus, Amazonas. Therefore, research was carried out using a quali-quantitative methodology, which aimed to analyze the situation of sick leave of teachers linked to the District Division Zona Centro-Sul, of the Municipal Department of Education, in Manaus, from 2017 to 2019. In addition, the absence rates that occurred each year were verified, the average time of absence, considering aspects such as CID, gender and work function, the identification of the main CIDs that led to the removal of professors from their activities was also carried out. labor and which were supported by a medical report. Regarding the reality investigated in the DDZ Centro-Sul, from SEMED/Manaus, it was noticed that teachers dispensed with sick leave or even postponed surgeries to end the school year. These professionals put their health in the background, often causing more wear and tear and stress.